Determination of the influence of liquid molecule structure on acoustic absorption quantity - LINDE, Bogumił; KOSMOL, Marek; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1986)
This paper is concerned with the propagation mechanism of ultrasonicwaves. It was aimed at the determination of relation the values of the absorption coefficient (a /f^2)_rel and the structure of liquid molecules. Such relation were observed in the course of investigations performed on cyclic compounds [1-4].